Demographic and clinical characteristics of patients involuntarily hospitalized in an Italian psychiatric ward: a 1-year retrospective analysis: Characteristics of patients involuntarily hospitalized in an Italian psychiatric ward - Di Lorenzo, Rosaria; Vecchi, Laura; Artoni, Cecilia; Mongelli, Francesca; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2018)
Background: In Italy, psychiatric compulsory treatments are regulated by Law 180 of 13-5-1978 that establishes three criteria: 1) acute psychiatric conditions requiring urgent treatment, 2) patient’s refusal of treatment, 3) inpatient treatment is necessary and cannot be postponed. Aim: To highlight demographic and clinical risk factors for involuntary treatments. Methods: We retrospectively collected all hospitalizations in the Service of Psychiatric Diagnosis and Treatment of a northern Italian town from 1-1-2015 to 31-12-2015. We statistically compared demographic and clinical variables related to voluntarily and involuntarily admitted patients and their hospitalizations. Results: We divided our sample into patients voluntarily hospitalized (PVH=236) and involuntarily (PIH=160) according to their voluntary (VH= 304) and involuntary (IH=197) hospitalizations. PIH were older than PVH and, more frequently, lived alone and were unemployed (p